Junie B., first grader : boss of lunch - Park, Barbara; Brunkus, Denise (New York : Random House, 2002)
Junie, an outspoken, sometimes exasperating, first grader is thrilled when she is told she can help out in the school cafeteria.
"A Stepping Stone book."
330
Accelerated Reader AR
Keywords: Schools -- Juvenile fiction; School lunchrooms, cafeterias, etc. -- Juvenile fiction; Humorous fiction